Implementasi Fuzzy Menggunakan Mamdani Pada Sistem Pendukung Keputusan Lokasi Pemasangan Iklan Calon Legislatif - Syahputra, Wisnu (TIN: Terapan Informatika Nusantara, 2022)
The development of information technology today requires information that is fast and accurate in its implementation. The installation of prospective legislative advertising brochures that perform well with the support of a decision support system is one of the implementations of the development of information technology. Research that uses the mamdani method in this decision support system produces a decision support system application for installing banners that are commonly used in legislative candidates. The criteria used in the decision support system for installing advertising banners are: location name, strategy element, location location, rival advertisement and population. The results of this study are the location of the selected strategies from several places that have good performance that have followed the selection, and the output of the application helps decision makers (desician makers) in choosing alternatives for the location of advertisements in the form of banner candidates using desktop-based web applications